Biomasa microbiana y respiración basal del suelo bajo sistemas agroforestales con cultivos de café (2019)
The microbiological activity is essential to maintain soil quality, and agroforestry systems emerge as an alternative to the agro-ecological and sustainable land management. This work evaluated the effect of the Caturra and Catuaí coffee varieties, and the weather fl uctuation on some microbiological properties of the soil, as indicators of quality in an agroforestry system. The soil samples were taken from the top layer with a depth of 5cm, during a year in dry and rainy seasons. The highest CO2 emissions were observed in soils with the Catuaí variety, in the dry season. On the other hand, Carbon levels of the microbial biomass (Cmic) did not show differences between the variables studied. The values obtained for the metabolic quotient (qCO2) were higher in soils with the Catuaí variety; while the micro-bial quotient (qMic) presented the highest values in soils with the Caturra variety. The metabolic efficiency ratio (qCO2.Corg-1) showed no differences between the studied soils, however, their levels were higher for the samples taken during the dry season. Soil microbiota showed sensitivity to changes by climatic period and by the type of variety, while the constant eco-physiological were substantially appropriate to evaluate soil quality and sensitive to changes by cli-matic period and variety of coffee grown in these agroecosystems.